2006
DOI: 10.1158/0008-5472.can-05-3252
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Impairs CD4+ T Cell Activation by Inhibition of lck: Implications in Hodgkin's Lymphoma

Abstract: Many tumors, including Hodgkin's lymphoma, are associated with decreased cellular immunity and elevated levels of prostaglandin E 2 (PGE 2 ), a known inhibitor of CD4 + T cell activation, suggested to be involved in immune deviation in cancer. To address the molecular mechanisms tumor-derived PGE 2 might have on primary human CD4 + T cells, we used a whole genome-based transcriptional approach and show that PGE 2 severely limited changes of gene expression induced by signaling through the T cell receptor and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 55 publications
5
66
0
4
Order By: Relevance
“…TARC (CCL17), IL-13, CD80, CD86, and CD40-CD40L interactions all contribute to the formation of tumor infiltrating T cells. HRS cells also produce some immunosuppressive factors (IL-10, TGF-b, galectin-1, and prostaglandin E2) [69][70][71], whereas CD95/FAS ligand expressed by HRS cells stimulate the apoptosis of activated Th1 and CD8 þ T cells. Tregs also produce IL-10, which indirectly contributes to the protection against cytotoxic T and NK cells [63].…”
Section: Tumor Infiltrating T Cells Hrs Cells Are Surrounded Mostly Bmentioning
confidence: 99%
“…TARC (CCL17), IL-13, CD80, CD86, and CD40-CD40L interactions all contribute to the formation of tumor infiltrating T cells. HRS cells also produce some immunosuppressive factors (IL-10, TGF-b, galectin-1, and prostaglandin E2) [69][70][71], whereas CD95/FAS ligand expressed by HRS cells stimulate the apoptosis of activated Th1 and CD8 þ T cells. Tregs also produce IL-10, which indirectly contributes to the protection against cytotoxic T and NK cells [63].…”
Section: Tumor Infiltrating T Cells Hrs Cells Are Surrounded Mostly Bmentioning
confidence: 99%
“…RNA isolation and quantification were performed as described previously (25). cRNA (1.5 g) was hybridized to BeadChip Arrays (MouseWG-6 v2 Expression BeadChip; Illumina) and scanned on Illumina BeadStation 500 X.…”
Section: Mrmentioning
confidence: 99%
“…Macrophages in patients with Hodgkin's lymphoma highly produce PGE 2 , which can suppress cell-mediated immunity [30,31]. In a small study, Hazar et al demonstrated that in 70% of Hodgkin's patients' HRS cells expressed Cox-2 [32].…”
Section: Hodgkin's Lymphomamentioning
confidence: 99%